Short contacts between chains enhancing luminescence quantum yields and carrier mobilities in conjugated copolymers - Tudor H. Thomas (Nature Portfolio, 2019)
Designing conjugated polymers with high charge carrier mobility and fluorescence quantum efficiency, though attractive for optoelectronics, remains challenging. Here, the authors report a strategy for designing donor-acceptor copolymers whose optoelectronic properties exceed the state-of-the-art.